2018
DOI: 10.1016/j.echo.2018.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Three-Dimensional Echocardiography of the Left Ventricle—Pediatric Percentiles and Head-to-Head Comparison of Different Contour-Finding Algorithms: A Multicenter Study

Abstract: RT3DE allows reproducible noninvasive assessment of LV volumes and function. However, intertechnique variability is relevant. Therefore, our software-specific percentiles, based on a large pediatric population, serve as a reference for both commonly used quantification programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
33
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 33 publications
9
33
2
1
Order By: Relevance
“…Prior to the start of the study, standardization of the acquisition procedure, including presets and operator training, took place. 16,17 Fullvolume 3DE data sets were obtained from an apical approach based on standard recommendations. 18 A full-volume scan was acquired from four to seven R-wave triggered subvolumes.…”
Section: Three-dimensional Echocardiographymentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to the start of the study, standardization of the acquisition procedure, including presets and operator training, took place. 16,17 Fullvolume 3DE data sets were obtained from an apical approach based on standard recommendations. 18 A full-volume scan was acquired from four to seven R-wave triggered subvolumes.…”
Section: Three-dimensional Echocardiographymentioning
confidence: 99%
“…Additionally, Buechel et al 33 as well as our working group demonstrated that vendor-dependent and vendorindependent software can have an impact on the resulting data derived from 3DE. 16,32 Therefore, it might be suggested that the same software should be used for longitudinal analysis in the same subjects and for cross-sectional studies.…”
Section: Reference Valuesmentioning
confidence: 99%
“…One of the most important clinical issues concerns reference values for volumetric and functional LV parameters in 3D-ECHO, which have not yet been agreed upon; with many publications advocating different values for the paediatric population [19][20][21][22][23]. Even LVEF was found to be disputable in this regard.…”
Section: Left Ventricular Functionmentioning
confidence: 99%
“…Even LVEF was found to be disputable in this regard. The paper by Krell et al [23] based on 3D-ECHO results obtained from 370 healthy children proposed mean LVEF values ranging from 61.5% ± 5.1% to 62.7% ± 5.9%, depending on the software used for analysis (QLab by Philips, Amsterdam, Netherlands and Image Area by TomTec, Unterschleissheim, Germany). Kuebler et al [22] have recently proposed a lower LVEF limit (51%), which seems to be logical considering the consistency of 3D-ECHO results with CMR adopting similar ranges.…”
Section: Left Ventricular Functionmentioning
confidence: 99%
“…We read with interest the letter of Cantinotti et al 1 containing feedback on our recently published report. 2 We consider this topic to be crucial for the clinical application of echocardiography and appreciate their work and publications in the field of pediatric echocardiographic nomograms. 3 Reliable reference data and nomograms are essential tools for quantification in pediatrics and pediatric cardiology.…”
mentioning
confidence: 99%